Optimization of Shrinkage and Mechanical Properties in Continuous Glass Fiber-Reinforced Polypropylene Composite I-Beams during Pultrusion Process - Ma, Huihuang; Wang, Zijian; Fu, Yizhao; Luo, Luo; Zhou, Xiaodong (Journal of Composites and Biodegradable Polymers, 2025)
This study addresses shrinkage marks in pultruded continuous glass fiber-reinforced polypropylene I-beams by modifying the cooling mold with compensation segments, adding nano-SiO₂ as a nucleating agent, and incorporating glass fiber mesh. Under optimized conditions (80 mm/min, 235°C, 65–85–105°C), a compensation segment of 85 mm length and 0.5 mm depth effectively reduced surface shrinkage. Adding 2 wt% nano-SiO₂ lowered vertical shrinkage from 3.07% to 1.15% and horizontal shrinkage from 1.57% to 0.23%. An 8-mesh glass fiber grid further improved dimensional stability while maintaining a bending failure load of 5132.26 N and yield load of 3090 N. These strategies collectively enhance dimensional accuracy and mechanical performance in thermoplastic composite I-beams.